PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Devilia Devilia; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate governance on firm performance. The independent variables in this study are managerial ownership, institutional ownership, number of meetings of the Board of Commissioners, size of the Board of Commissioners and the Audit Committee. Meanwhile, the dependent variable is the firm performance as measured by return on asset (ROA) and return on equity (ROE). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sampling method used was purposive sampling method. This study used 119 samples of companies that met predetermined criteria. The data used are secondary data in the form of financial reports and annual reports obtained through www.idx.co.id and financial information obtained from Bloomberg laboratories. The statistical test used in this study is multiple linear regression analysis.The results of statistical tests show that managerial ownership has a significant negative effect on firm performance, Meanwhile, institutional ownership and the Audit Committee have no effect on firm performance. The number of Board of Commissioners meetings has no effect on ROA but has a positive effect on firm performance as measured by ROE. The size of the Board of Commissioners has a positive influence on firm performance.